Sonographic features differentiating early-stage ovarian clear cell carcinoma from endometrioma with atypical features - Kuan-Ju Huang; Ying-Xuan Li; Chin-Jui Wu; Wen-Chun Chang; Lin-Hung Wei; Bor-Ching Sheu (BMC, 2022)
Abstract Background Ovarian clear cell carcinoma (OCCC) is the most common endometriosis-associated ovarian cancer. Ovarian endometriosis may present with atypical or malignant sonographic features and interfere with clinical judgment about whether definitive surgical intervention is required. Objective To compare the characteristics of endometrioma with atypical features and OCCC. Methods This study enrolled patients with pathologic diagnoses of either endometrioma or OCCC. For patients with endometrioma, only those with atypical features, defined as the presence of at least one of the following sonographic characteristics: cyst diameter of 10 ± 1 cm, multi-cystic lesions, any solid component or papillary structure, and blood flow of any degree, were included. Results Sixty-three patients had endometriomas with atypical features, while 57 patients had OCCC. Patients with endometriomas were younger (39.33 ± 7.04 years vs. 53.11 ± 9.28 years, P < 0.01), had smaller cysts (7.81 ± 2.81 cm vs. 12.68 ± 4.60 cm, P < 0.01), and had smaller solid components (0.93 ± 1.74 cm vs. 4.82 ± 3.53 cm, P < 0.01). In contrast, OCCCs were associated with loss of ground-glass echogenicity (6.3% vs 68.4%, P < 0.01). In multivariate analysis, advanced age (> 47.5 years), large cysts (> 11.55 cm), large solid components (size > 1.37 cm), and loss of ground-glass echogenicity were independent factors suggestive of malignancy. Conclusion Advanced age, larger cyst sizes, larger solid component sizes, and loss of ground-glass echogenicity are major factors differentiating endometriomas from malignancies. For women in menopausal transition who have finished childbearing who present with endometrioma with atypical features, removal of the adnexa intact could be considered.